Onion waste based-biorefinery for sustainable generation of value-added products. (October 2022) - Sagar, Narashans Alok; Kumar, Yogesh; Singh, Ramveer; Nickhil, C.; Kumar, Deepak; Sharma, Praveen; Om Pandey, Hari; Bhoj, Suvarna; Tarafdar, Ayon
Graphical abstract: Highlights: Onion waste is generated through industrial, domestic and postharvest losses. Fermentation, extraction and hydrolysis are mostly used for onion waste biorefineries. Organic acids, pigments, and bioactives can be generated from onion waste. Chemico-mechanical methods for different onion waste classes are currently needed. Co-production of acids, polyphenols or enzymes from onion waste may be attempted. Abstract: Waste derived from the onion processing sector can be harnessed for the production of organic acids, polyphenols, polysachharides, biofuels and pigments. To sustainably utilize onion processing residues, different biorefinery strategies such as enzymatic hydrolysis, fermentation and hydrothermal carbonization have been widely investigated. This review discusses the recent advances in the biorefinery approaches used for valorization of onion processing waste followed by the production of different value-added products from diverse classes of onion waste. The review also highlights the current challenges faced by the bioprocessing sector for the utilization of onion processing waste and perspectives to tackle them.